PROBLEMATIKA KETUNTASAN MOTORIK DAN DAMPAKNYA TERHADAP KEMANDIRIAN ANAK DI BUSTANUL ATHFAL ‘AISYIYAH KARANGPATIHAN PULUNG PONOROGO DALAM PERSPEKTIF PENDIDIKAN AGAMA ISLAM - Sholihah, Ita Roni Sholihah; Maida, Hanik Rista Maida; Arif, Muhammad Zainal Arif; Kurnianto, Rido Kurnianto (TARBAWI:Journal on Islamic Education, 2024)
Motoric education aims to help students become independent and responsible, and acts as a lifelong investment. This research examines the completeness of early childhood motoric education in Bustanul Athfal 'Aisyiyah Karangpatihan Pulung Ponorogo with a focus on the program, implementation, problems and impact on children's independence. Using qualitative methods with interviews, observation and documentation, this research involved school principals, teachers, parents and students. The results of the research show that motor skills are the foundation for early childhood learning, help develop children's character and potential, increase concentration, and become the basis for children's independent education.